Effect of Okara on Physicochemical and Sensory Properties of Soda Cracker - Mansoor Abdul Hamid; Fong Suk Zean; Yeap Chi Hong; Sugianto Sugianto (Universitas Negeri Malang, 2023)
Using Okara flour, this study evaluates its effect on the quality of soda crackers. Nine formulations were produced; namely, the cracker with 15, 20, and 25 percent okara flour was developed with 8, 10, and 12 percent margarine, respectively. Four formulations were chosen using the BIB test on the mean score. The best okara cracker was identified through a hedonic test by trained panelists based on the attributes of color, aroma, taste, texture, crispness, and overall acceptance. Proximate analysis was conducted on the best formulation showing that the best recipe consisted of 6.44 percent moisture, 12.96 percent protein, 8.65 percent fat, 2.41 percent ash, 2.35 percent crude fiber, 67.30 percent carbohydrate, 14.62 percent dietary fiber, and 428.12 kcal/g energy content. The color of the best formulation was significantly (p less than 0.05) darker than the control sample due to its high protein content. Therefore, the rate of Millard reaction had increased compared to the control sample. Additionally, the hardness and fracturability of the okara cracker were found to be significantly (p less than 0.05) higher than the control sample, mainly due to the high protein content in the cracker. The stack height decreased as okara content increased high water absorption and weak gluten formation. Hence, it could be claimed as a product with high dietary fiber and a source of protein.